(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Population growth and technological advancements are driving a fast increase in global energy demand and traditional sources of energy, such as diesel or coal-fired power plants and nuclear-powered heat-power stations, dominate the world’s energy output. Renewables contributed 19% to human energy consumption and 22% to the generation of electricity in 2012 and 2013, according to REN21’s 2014 report. Traditional biomass accounts for 9% of this energy consumption, 4.2% for non-biomass heat energy, 3.8% for hydroelectricity, and 2% for wind, solar, and geothermal electricity. In some long-term scenarios, a considerable increase in the percentage of renewable technologies is expected. If appropriate laws and technical advancements are enacted, renewable energy sources might satisfy up to 50% of the world’s energy demands by the middle of the twenty-first century. It has become more vital for the advancement of civilization in recent years that we use biomass energy to generate electricity. Sustainable development has become a reality due to global warming, resource depletion, and other worldwide issues. Biomass can be a key source of renewable energy for electrical power plants. PV (solar)-biomass hybrid technology is studied in this article as an alternative to relying on the grid. This hybrid plant might be a viable alternative for places with modest solar availability but plentiful biomass. Using sun insolation to limit the usage of biomass can enhance the output of a power plant. The biomass system will be employed when solar thermal energy is insufficient.